Purchasing Power Parities in Five East African Countries : Burundi, Kenya, Rwanda, Tanzania, and Uganda - Krichene, Noureddine (IMF Working Papers; Working Paper, 1998)
In a case study of Burundi, Kenya, Rwanda, Tanzania, and Uganda, this paper finds that bilateral real exchange rates revert to a long-term equilibrium in line with purchasing power parities, implying that these countries constitute an integrated trading zone, their markets are interdependent and arbitrage works efficiently, and intraregional competitiveness is preserved. These findings are partly explained by the flexibility of nominal exchange rates and prices and the absence of long-term productivity differences among these countries. To strengthen market integration, foster private sector development, and enhance growth prospects, the paper emphasizes the importance of increased trade, competitive labor markets, flexible exchange rates, and convergence of macroeconomic and structural policies.